High‐level expression of xyloglucanase B from Rhizomucor miehei and its application in the preparation of partially hydrolyzed apple pomace xyloglucan. Issue 2 (26th May 2022) - Wang, Nan‐nan; Li, Yan‐xiao; Zhu, Chun‐hua; Yan, Qiao‐juan; Shi, Ran; Jiang, Zheng‐qiang
Abstract: A xyloglucanase gene ( RmXEG12B ) was cloned from Rhizomucor miehei CAU432 and successfully expressed in Pichia pastoris . The highest xyloglucanase activity of 26, 200 U/mL was achieved after 168 h high‐cell‐density fermentation. The optimal pH and temperature of RmXEG12B were 5.0 and 55°C, respectively. RmXEG12B showed good stability within pH of 3.0–10.0 and was stable up to 50°C. It exhibited the highest specific activity (5989.3 U/mg) towards tamarind xyloglucan. RmXEG12B hydrolyzed apple pomace xyloglucan to produce the partially hydrolyzed apple pomace xyloglucan, which demonstrated a weight average molecular weight of 1.6 × 10 4  Da and contained three major oligosaccharides with a degree of polymerization of 7–10. This is a strategy for the comprehensive utilization of apple pomace to produce the partially hydrolyzed apple pomace xyloglucan. Abstract : A xyloglucanase gene (RmXEG12B) from Rhizomucor miehei CAU432 was successfully expressed in Pichia pastoris . RmXEG12B hydrolyzed apple pomace xyloglucan to produce the partially hydrolyzed apple pomace xyloglucan. This is a strategy for the comprehensive utilization of apple pomace to produce the partially hydrolyzed apple pomace xyloglucan